The Impact of Company Financial Performance and Audit Fees on the Disclosure of Key Audit Matters (KAM) - Novia Gita Rhamadhani; Dina Heriyati (Institute of Research and Community Outreach - Petra Christian University, 2025)
Key Audit Matters (KAM), recently mandated by ISA 701, aim to enhance audit transparency by addressing critical audit areas. This study provides empirical evidence on the impact of financial performance and audit fees on KAM disclosures. Furthermore, it categorizes KAM into two risk levels: Entity-Level Risk (ELRKAM) and Account-Level Risk (ALRKAM). The data analyzed consist of 1,080 firm observations listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023. The researchers conducted panel data regression analysis using EViews 12.0. The findings reveal that financial performance has no significant impact on the overall KAM or ELRKAM disclosures but does affect ALRKAM. This indicates that auditors focus more on specific risk areas rather than on overall financial performance. On the other hand, we find that audit fees positively influence the disclosure of overall KAM and ELRKAM, but they have no effect on ALRKAM. These results suggest that higher audit fees contribute to enhanced transparency regarding overall risks but do not necessarily affect the disclosure of specific account-level risks.